Reliability analysis and redundancy design of smart grid wireless communications system for demand side management - Niyato, Dusit (2013)
To ensure efficient, continuous, and secure operation of the next generation smart power grid, the reliability of its data communications system, and in particular, the wireless communications system will be crucial. In this article, we present a reliability analysis of the wireless communications system in the smart grid to support demand-side management (DSM). The availability performance, which is the probability that the wireless connectivity between a smart meter to the meter data-management system (MDMS) is available, is obtained given the random failure of the system devices. This availability measure is then used to calculate the cost of power-demand estimation error and damage of power distribution equipment if its failure cannot be reported. At this end, redundancy design approaches are presented to minimize the cost of failure as well as the cost of deployment of the wireless communications system in the smart grid.